2020
DOI: 10.1371/journal.ppat.1008773
|View full text |Cite
|
Sign up to set email alerts
|

NS5-V372A and NS5-H386Y variations are responsible for differences in interferon α/β induction and co-contribute to the replication advantage of Japanese encephalitis virus genotype I over genotype III in ducklings

Abstract: Japanese encephalitis virus (JEV) genotype I (GI) replicates more efficiently than genotype III (GIII) in birds, and this difference is considered to be one of the reasons for the JEV genotype shift. In this study, we utilized duck embryo fibroblasts and domestic ducklings as in vitro and in vivo models of a JEV amplifying avian host to identify the viral determinants of the differing replication efficiency between the GI and GIII strains in birds. GI strains induced significantly lower levels of interferon (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 65 publications
0
22
1
Order By: Relevance
“…In the present study, of nine samples harboring JEV sequences, six samples contained JEV sequences mostly matched with GI strains, in agreement with a previous study conducted in Yunnan province, in which GI is identified as the dominant genotype ( Xiao et al, 2018a ). The previous studies indicate that GI strains have higher replication efficiency in birds and pigs than GIII strains ( Fan et al, 2019 ; Li et al, 2020 ), and the emergence and continuous circulation of GI strains could be permanent threats for pigs as well as for poultry. Development of precautionary measures, such as GI vaccine, in advance is needed to avoid future outbreaks due to this newly emerging genotype ( Wei et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, of nine samples harboring JEV sequences, six samples contained JEV sequences mostly matched with GI strains, in agreement with a previous study conducted in Yunnan province, in which GI is identified as the dominant genotype ( Xiao et al, 2018a ). The previous studies indicate that GI strains have higher replication efficiency in birds and pigs than GIII strains ( Fan et al, 2019 ; Li et al, 2020 ), and the emergence and continuous circulation of GI strains could be permanent threats for pigs as well as for poultry. Development of precautionary measures, such as GI vaccine, in advance is needed to avoid future outbreaks due to this newly emerging genotype ( Wei et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…JEV replicates in eukaryotic cells, such as swine testicular (ST), human embryonic kidney 293T (HEK293T) and baby hamster kidney (BHK) cell lines [ 15 ]; we therefore used a eukaryotic cell model to identify the sites cleaved by NS2B-NS3 protease in the JEV polyprotein. The artificial GFP substrates for JEV NS2B-NS3 protease were constructed by inserting the predicted cleavage site sequences of the JEV GIII strain ( Figure 1 B) into GFP at the position between residue 173 and 174 ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…JEV replicates in susceptible eukaryotic cells, such as ST, BHK and HEK293T cells [ 15 ], which were supposed to be suitable as in vitro models for mapping the cleavage sites mediated by NS2B-NS3 protease in JEV polyprotein. However, we observed that host cell protease cleaved the sites predicted to be cleaved by NS2B-NS3 protease in ST, BHK and HEK293T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interaction of NS5 with cyclophilins and the corresponding inhibition by cyclosporins [ 43 ], Hsp70 [ 44 ], and with a great number of proteins related to the regulation of the immune system has been described [ 45 ]. In fact, most flavivirus NS5 interactions described so far are with proteins related to the interferon response [ 46 ], such as Hsp90 and JAK/STAT, among others [ 47 , 48 , 49 , 50 ]. It seems that the nuclear location of NS5 is not relevant to this type of modulation of the immune response [ 51 ].…”
Section: Discussionmentioning
confidence: 99%